The Epithelial-to-Mesenchymal Transition as a Possible Therapeutic Target in Fibrotic Disorders - Di Gregorio, Jacopo; Robuffo, Iole; Spalletta, Sonia; Giambuzzi, Giulia; De Iuliis, Vincenzo; Toniato, Elena; Martinotti, Stefano; Conti, Pio; Flati, Vincenzo (Frontiers in Cell and Developmental Biology, 2020)
Fibrosis is a chronic and progressive disorder characterized by excessive deposition of extracellular matrix, which leads to scarring and loss of function of the affected organ or tissue. Indeed, the fibrotic process affects several organs and tissues, with specific molecular background. However, two common hallmarks are shared: the crucial role of the transforming growth factor-beta (TGF-β) and the involvement of the inflammation process, that is essential for initiating the fibrotic degeneration. TGF-β in particular but also other cytokines regulate the most common molecular mechanism at the basis of fibrosis, the Epithelial-to-Mesenchymal Transition (EMT). EMT has been extensively studied, but not yet fully explored as a possible therapeutic target for fibrosis. A deeper understanding of the crosstalk between fibrosis and EMT may represent an opportunity for the development of a broadly effective anti-fibrotic therapy. Here we report the evidences of the relationship between EMT and multi-organ fibrosis, and the possible therapeutic approaches that may be developed by exploiting this relationship.